2020
DOI: 10.31577/caosp.2020.50.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Stark broadening and atomic data for Ar XVI

Abstract: Stark broadening and atomic data calculations have been developed for the recent years, especially atomic and line broadening data for highly ionized ions of argon. We present in this paper atomic data (such as energy levels, line strengths, oscillator strengths and radiative decay rates) for Ar XVI ion and quantum Stark broadening calculations for 10 Ar XVI lines. Radiative atomic data for this ion have been calculated using the University College London (UCL) codes (SUPERSTRUCTURE, DISTORTED WAVE, JAJOM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…That is, aer approximately 1 × 10 −3 s, the data acquisition was stopped, and then the acquired data were stored in a computer and integrated to generate the spectra. Based on the spectral data, the Boltzmann plot method and the Stark broadening method were used to calculate the plasma electron temperature and plasma electron density, respectively, [26][27][28] to nally verify the correctness of the plasma expansion model.…”
Section: Research On Plasma Characteristics Of Laser Processing Bronz...mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, aer approximately 1 × 10 −3 s, the data acquisition was stopped, and then the acquired data were stored in a computer and integrated to generate the spectra. Based on the spectral data, the Boltzmann plot method and the Stark broadening method were used to calculate the plasma electron temperature and plasma electron density, respectively, [26][27][28] to nally verify the correctness of the plasma expansion model.…”
Section: Research On Plasma Characteristics Of Laser Processing Bronz...mentioning
confidence: 99%
“…8 , and the slope value for the line was determined to be approximately −1.375. The Boltzmann plot method 28 shows that T e = −1/( k b X S ), where X S is the value of the slope of the straight line. By substituting the slope value ( X S ) into the temperature equation, the plasma electron temperature was calculated to be approximately 8438 ± 840 K. The calculation error is approximately 10%, which is mainly attributed to the measurement error, parameter error, and data fitting error.…”
Section: Experiments For the Nanosecond Laser Processing Of Materialsmentioning
confidence: 99%
“…To perform the line broadening calculations, we have used our quantum mechanical method (Elabidi et al 2004. We applied this method many times (Aloui et al 2018(Aloui et al , 2019b(Aloui et al , 2020(Aloui et al , 2021, and we found that it gives accurate results compared to other approaches that can be used with confidence in plasma diagnostic. Present calculations have been performed at electron density 𝑁 𝑒 = 10 17 cm −3 and for electron temperatures between 10 4 K and 5 × 10 5 K. Stark width results for Sr V and Sr VI are missing in the literature despite their importance for stellar plasma investigation.…”
mentioning
confidence: 99%